2018
DOI: 10.1371/journal.pone.0191582
|View full text |Cite
|
Sign up to set email alerts
|

Brain entropy and human intelligence: A resting-state fMRI study

Abstract: Human intelligence comprises comprehension of and reasoning about an infinitely variable external environment. A brain capable of large variability in neural configurations, or states, will more easily understand and predict variable external events. Entropy measures the variety of configurations possible within a system, and recently the concept of brain entropy has been defined as the number of neural states a given brain can access. This study investigates the relationship between human intelligence and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
63
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 42 publications
(52 reference statements)
11
63
2
1
Order By: Relevance
“…These regions are known to be influential on fluid intelligence [33,39,41]. In addition, fluid intelligence is related to activity in the bilateral superior, inferior, and middle frontal gyri, as well as the anterior cingulate and paracingulate cortex [41]. The selected features corroborate with these past studies.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These regions are known to be influential on fluid intelligence [33,39,41]. In addition, fluid intelligence is related to activity in the bilateral superior, inferior, and middle frontal gyri, as well as the anterior cingulate and paracingulate cortex [41]. The selected features corroborate with these past studies.…”
Section: Discussionsupporting
confidence: 81%
“…The group mean correlation of nMSE with fluid intelligence was negative at fine scales and positive at coarse scales. Recent studies have shown the FC and SampEn have a similar correlation trend [34,36,42,43], and FC had a positive correlation with fluid intelligence [10,39,41,44]. In addition, studies have shown that fluid intelligence depends on synchrony in the brain's intrinsic network [45].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Cognitive processing is sometimes defined over the information-theoretic properties of the neural vehicles. Saxe et al (2018) describe how brain entropy during resting state, as measured by fMRI, correlates with general intelligence. Chang et al (2018) describe how drinking coffee increases the brain's entropy during resting state.…”
Section: Connections Via Empirical Correlationsmentioning
confidence: 99%